Personal Data Broker: A Solution to Assure Data Privacy in EdTech - Amo, Daniel; Fonseca, David; Alier, Marc; García-Peñalvo, Francisco José; Casañ, María José; Alsina, María (Springer International Publishing, 2019)
Educational technologies (Edtech) collect private and personal data from students. This is a growing trend in both new and already available Edtech. There are different stakeholders in the analysis of the collected students’ data. Teachers use educational analytics to enhance the learning environment, principals use academic analytics for decision making in the leadership of the educational institution and Edtech providers uses students’ data interactions to improve their services and tools. There are some issues in this new context. Edtech have been feeding their analytical algorithms from student’s data, both private and personal, even from minors. This draws a critical problem about data privacy fragility in Edtech. Moreover, this is a sensitive issue that generates fears and angst in the use of educational data analytics in Edtech, such as learning management systems (LMS). Current laws, regulations, policies, principles and good practices are not enough to prevent private data leakage, security breaches, misuses or trading. For instance, data privacy agreements in LMS are deterrent but not an ultimate solution due do not act in real time. There is a need for automated real-time law enforcement to avoid the fragility of data privacy. In this work, we take a step further in the automation of data privacy agreement in LMS. We expose which technology and architecture are suitable for data privacy agreement automation, a partial implementation of the design in Moodle and ongoing work.
Keywords: Academic analytics; Blockchain; Data privacy; Digital identity; Educational data mining; Learning Analytics; Moodle; Smart contracts

Meeting the data challenge in education: A knowledge and innovation exchange - Crouch, Luis (Global Partnership for Education, 2019)
The purpose of this paper is to describe the current landscape in education data systems and spark discussion and debate around potential areas for KIX investment.
Keywords: ___working_potential_duplicate

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology, EdTech, low-income countries, literature review

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)

The EdTech Hub’s approach to amplifying impact through engagement – The EdTech Hub - Jamieson Eberhardt, Molly (EdTech Hub, 2019)
If you have spent time working in the education sector, you’ll know that even marginal gains are worthy of celebration. Those of us involved in launching the EdTech Hub know this well — from our experience as teachers, researchers, advisers, programme implementers, and civil servants. Nevertheless, we have the ambition to help accelerate progress toward quality education at an unprecedented rate. We of course know that sustainable change often takes time, and we respect hard-earned marginal gains. But what we’re really after is improvement in education outcomes at a pace that matches the urgency of the problem — think millions of children receiving quality education within a decade, not in decades.
Keywords: LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Factors affecting cloud computing adoption in the Indian school education system - Singh, Jewan; Mansotra, Vibhakar (Education and Information Technologies, 2019)
Cloud computing is becoming a leading trend worldwide, due to its enhanced reliability, scalability, flexibility, availability and processing throughput. However, the decision related to adoption of the cloud computing model is often complicated by challenges and uncertainties about the expected business value and its overall impact on the organisation. Till date, different contemporary technology acceptance theories and models have been used to test and validate adoption chances of cloud computing at organisational and individual levels. However, no experimental study has been conducted to provide a holistic evaluation of the determinants of cloud computing in the Asian world particularly in the context of the Indian school education system. Due to lack of such studies, we propose a theoretical model based on the TOE framework to explain the role of technological, organisational and environmental factors on the adoption of cloud computing in the Indian school education system. The data was collected from fifty-six 56 randomly selected secondary schools through questionnaire based survey to examine the relationship between the variables employing 5-points Likert scale. Reliability and validity measures were used to establish the quality and the usefulness of the collected data. In addition multi co-linearity test was also conducted. In order to test the research hypothesis, multiple regression analysis was conducted. The results indicate that relative advantage, compatibility, and complexity representing technological factors; top management support representing organisational factors; and competitive pressure, external expertise and attitude towards change representing environmental factors were found to have an positive and significant influence on the adoption of cloud computing services in the Indian school education system. The findings have a great significance since they can provide knowledge about cloud computing factors as well as insights and directions to the education policy planners and decision makers for successful adoption of cloud computing technology in India.

Bangladesh Education Sector Public Expenditure Review - Bhatta, Saurav Dev; Genoni, Maria Eugenia; Sharma, Uttam; Khaltarkhuu, Buyant Erdene; Maratou-Kolias, Laura; Asaduzzaman, T. M. (World Bank, 2019)
Adequate investment in human capital development is critical for enabling Bangladesh to reach its goal of becoming an upper middle-income country. Bangladesh, currently a lower-middle country with an annual per capita gross national income (GNI) of USD 1,470 (WDI 2019), aims to attain upper-middle income status by 2021 and eliminate poverty by 2030. Recognizing the importance of investing in education for building its human capital base, the government of Bangladesh (GoB) has been allocating a large portion of the national budget to the education sector each year during the past two decades. Effective utilization and equitable distribution of allocated public spending is important for ensuring adequate progress in education outcomes. This report analyzes major spending and outcomes trends in the overall education sector in recent years, with a focus on primary and secondary education. Responding to the recommendation of the 2015 Bangladesh Public Expenditure Review Update for more analytical work on public spending in different sectors, including education, the current study analyzes the trends in major education expenditures, access to education, quality of education, and disparities in education outcomes in the past two decades. It also looks at the composition of education expenditure, consistency between budget allocations and actual expenditures, equity in education spending, and potential links between spending and key educational outcomes. Because of data limitations, this report focuses mainly on primary and secondary education. It is expected that this analysis will add to the literature on investments in the Bangladesh education sector and inform discussions on identifying policy priorities and making resource allocation decisions in the sector.
Keywords: Education Budget; Education Expenditure; Education Outcomes; Equity in Education; Public Expenditure Review